Ecological Discourse and Balinese Wisdom in Children’s Literatur - Suari, A. A. Pt. (Jurnal Penelitian Agama Hindu, 2025)
This study addresses the diminishing transmission of traditional ecological knowledge among younger generations by examining how children’s literature can preserve and revitalize indigenous eco-philosophies. Focusing on the Balinese narrative Luh Ayu Manik Mas Nglawan Luu Plastik, the research investigates how environmental values grounded in the Hindu cosmology of Tri Hita Karana emphasizing harmony with the divine (parhyangan), with others (pawongan), and with nature (palemahan) are discursively constructed. Using a qualitative-interpretative method with an ecolinguistic framework informed by Haugen’s (1972) ecological model of language, this study analyzes lexical choices, narrative patterns, and dialogic interactions across three dimensions: ideological, sociological, and biological. The findings reveal that the narrative integrates cultural, spiritual, and environmental elements to construct a holistic ecological discourse, portraying rituals and symbols as tools of eco-theological conservation. The story demonstrates how language encodes ecological ethics while promoting eco-literacy among young readers. These insights highlight the potential of children’s literature to support culturally rooted environmental education and inform curriculum development. The study underscores the importance of incorporating indigenous worldviews into contemporary ecological discourse through education, storytelling, and language.